Construcción de una máquina de Goldberg para potenciar la observación y la descripción de estudiantes de grado sexto - Gualtero Martínez, Yuly Andrea; Patiño Alzate, Juan David; Rivera Vargas, Yuly Hadbleydy; Gómez Torres, Angélica María (Revista Científica, 2011)
Rude Goldberg machine is a device that consists of sequence of simple or complex movements with an ultimate goal, but appears to have the entertainment function of the beholder and designs, can be used in the classroom for teaching physics. In this way and space resulted in one of the seminars for the Physics Degree in the Universidad Pedagógica Nacional named Material laboratory Construction, it develops Goldberg Machine, whose main objective to enhance the skills of observation and description sixth grade students in the College Nuestra Señora de la Salette, the assessment of different types of movement on the machine and previously studied in physics class.